2014
DOI: 10.1007/s00395-014-0455-4
|View full text |Cite
|
Sign up to set email alerts
|

Brain natriuretic peptide is able to stimulate cardiac progenitor cell proliferation and differentiation in murine hearts after birth

Abstract: Brain natriuretic peptide (BNP) contributes to heart formation during embryogenesis. After birth, despite a high number of studies aimed at understanding by which mechanism(s) BNP reduces myocardial ischemic injury in animal models, the actual role of this peptide in the heart remains elusive. In this study, we asked whether BNP treatment could modulate the proliferation of endogenous cardiac progenitor cells (CPCs) and/or their differentiation into cardiomyocytes. CPCs expressed the NPR-A and NPR-B receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
60
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(73 citation statements)
references
References 46 publications
12
60
1
Order By: Relevance
“…We found that, in this strain of neonatal mice subjected to MI, periostin deficiency impaired the regenerative capacity of cardiomyocytes. Similar results were described by others using non-cardiovascular disease models, with recent studies showing that periostin promoted pancreatic exocrine regeneration and neural stem cell proliferation 34 , 35 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found that, in this strain of neonatal mice subjected to MI, periostin deficiency impaired the regenerative capacity of cardiomyocytes. Similar results were described by others using non-cardiovascular disease models, with recent studies showing that periostin promoted pancreatic exocrine regeneration and neural stem cell proliferation 34 , 35 …”
Section: Discussionsupporting
confidence: 88%
“…We found that, in neonatal mice, myocardial ANP was downregulated at 7 days after MI but was upregulated at 21 d. Schoensiegel et al 38 reported that plasma levels of the N-terminal propeptide of ANP were not increased in adult mice subjected to non-ischaemic MI for 4 weeks. In a recent report by Bielmann et al , 35 BNP stimulated cardiac progenitor cell proliferation and differentiation in murine hearts after birth and BNP administration induced heart regeneration. Becker et al 39 also demonstrated in vitro that ANP induced proliferation of neonatal murine cardiomyocytes.…”
Section: Discussionmentioning
confidence: 93%
“…After BNP treatment, the number of renal tubular epithelial cells increased by approximately 5%. This result is consistent with the finding that BNP is able to stimulate cardiac progenitor cell proliferation and differentiation in murine hearts after birth (Bielmann et al, 2015), which indicates that BNP can also promote the proliferation of renal tubular epithelial cells. Furthermore, our results showed that serum Scr and BUN levels significantly decreased in the BNP + I/R group compared with the I/R group.…”
Section: Discussionsupporting
confidence: 82%
“…A recent study demonstrated that BNP stimulates the differentiation of cardiac progenitor cells into cardiomyocytes in vitro, and that injection of BNP into the mouse heart increases the number of newly formed cardiomyocytes. 24) According to our results, serum BNP was the only factor that was associated with the increased expression of c-kit in native cardiac tissue and the c- tissue and in expanded cells: Conflicting results have been reported regarding differences in stem cell activity among different regions of the heart. Some reports have suggested that the main source of CSCs is the atrium, 13) especially the RA appendage; 9,12) however, another study demonstrated the opposite result.…”
Section: Discussionmentioning
confidence: 59%